A highly sensitive piezoresistive sensor based on CNT-rGO aerogel for human motion detection. (October 2021) - Zhu, Hao; Dai, Shengping; Zhou, Xiaoshuang; Dong, Xu; Jiang, Yaoyao; Chen, Yuewen; Yuan, Ningyi; Ding, Jianning
In recent years, Flexible sensors have emerged as a highly active field due to their promising applications in artificial intelligence systems and wearable health care devices. However, achieving a high sensitivity in a wide pressure range is still a challenge. Here, a three-dimensional network structure CNT-rGO aerogels were prepared by a hydrothermal redox method, which can effectively enhance the mechanical strength and enrich the electrical conductivity paths. Moreover, the CNT–rGO aerogel-based piezoresistive sensor exhibited a fast response time (∼300 ms), wide working range (0∼3.5 kPa −1 ), high sensitivity (11.8 kPa −1 ), and good stability (∼2000 cycles). So the piezoresistive sensor can be employed to monitor and distinguish both large motions (e.g., weight placed on the aerogel) and subtle motions (e.g., pronounce and pulse), which shows potential applications in measuring pressure distribution, distinguishing tiny stress changes, and monitoring human body motion.